Specificity of V˙o2max and the ventilatory threshold in free swimming and cycle ergometry: comparison between triathletes and swimmers. Issue 12 (23rd November 2005) - Roels, B; Schmitt, L; Libicz, S; Bentley, D; Richalet, J-P; Millet, G
Abstract : Objectives: To compare maximal heart rate (HRmax ), maximal oxygen consumption (V˙o 2 max ), and the ventilatory threshold (VT; %V˙o 2 max ) during cycle ergometry and free swimming between swimmers and triathletes. Methods: Nine swimmers and ten triathletes completed an incremental swimming and cycling test to exhaustion. Whole body metabolic responses were determined in each test. Results: The swimmers exhibited a significantly higher V˙o 2 max in swimming than in cycling (58.4 (5.6) v 51.3 (5.1) ml/kg/min), whereas the opposite was found in the triathletes (53.0 (6.7) v 68.2 (6.8) ml/kg/min). HRmax was significantly different in the maximal cycling and swimming tests for the triathletes (188.6 (7.5) v 174.8 (9.0) beats/min). In the maximal swimming test, HRmax was significantly higher in the swimmers than in the triathletes (174.8 (9.0) v 184.6 (9.7) beats/min). No significant differences were found for VT measured in swimming and cycling in the triathletes and swimmers. Conclusion: This study confirms that the exercise testing mode affects the V˙o 2 max value, and that swimmers have very specific training adaptations even compared with triathletes. This may be a function of acute physiological responses combined with the specialist training status of the different athletes influencing maximal cardiac output or oxygen extraction. In contrast, the different training regimens do not seem to influence the VT, as this variable did not differ between the two testing modes in either group.